Body dysmorphic disorder and depression among male undergraduate students in a Malaysian University - Kang, Waye Hann; Loo, Min Yee; Leong, Xue Min; Ooi, Yi Fan; Teo, Wen Qi; Neoh, Teng Jun; Ling, Wei Chih (Frontiers in Psychiatry, 2022)
Introduction: Body dysmorphic disorder (BDD) and depression have been reported to be both prevalent among young people worldwide, resulting in serious implications in their quality of life and social functioning. This is worrying especially in men where mental disorders are often overlooked and under-researched. This study aims to determine the proportion of male university students with symptoms suggestive of body dysmorphic disorder and depression, as well as their perception on their body image. Methods: In this cross-sectional study, 1308 male students between the aged of 17-26 years in a private university in Malaysia via self-administered online questionnaire comprising the Patient Health Questionnaire (PHQ)-9, the Body Dysmorphic Disorder Questionnaire (BQQD) and the Body Self-Image Questionnaire (BSIQ), in addition to their sociodemographic parameters. Data analyses were performed with Mann Whitney test, chi square test and Fischer’s test. Results: 3.3% and 54.2% of the students had symptoms suggestive of BDD and depression respectively, with up to 9.02% of the students reporting having moderate to severe depression. There was a significant association between BDD symptoms and students staying alone, whilst depression was significantly associated with studying in the rural campus. Furthermore, a significant association was demonstrated between presence of BDD and depression symptoms. Most of the students were dissatisfied with their whole body, especially their height. Conclusion: The proportion of BDD and depression symptoms among male students in our university is quite high. Universities and the public health sector should develop better support service targeting male university students.